A study to evaluate the functional outcome of supracondylar intercondylar fracture femur fixed by open reduction internal fixation using distal femoral locking plates in a tertiary care centre - Roby, Ashwin; M., Nasneem; Mathew , Arun Mammen (International Journal of Research in Orthopaedics, 2025)
Background: Supracondylar Intercondylar fractures frequently exhibit greater complexity than supracondylar fractures and may result in considerable complications if not appropriately managed. The present study assessed the benefit of open reduction internal fixation (ORIF) of supracondylar-inter-condylar fracture femur using distal femoral locking plates in terms of functional outcome of the patient. Methods: The present descriptive study conducted in a tertiary healthcare centre located in Kollam, Kerala. The study included patients suffering from supracondylar intercondylar fracture femur fixed by ORIF using distal femoral locking plates. The patients were treated and assessed using range of motion, Knee society score and time taken for weight bearing. These findings were then compared for association with demographic and clinical variables. The data was analysed using chi-square test and p<0.05 was considered as statistically significant. Results: The study involved a total of 63 patients with supra-condylar intercondylar femur fractures, with most being females over 70 years old. Postoperatively, most patients showed a range of motion of 91-120 degrees, and the time for radiological union was less than 6 months. The mean KSS score improved significantly at 12 months, with the majority having excellent scores. The study also found significant differences in mean range of motion based on age, type of fracture, and open/closed fractures. The time taken for full weight bearing was also associated with the type of AO fractures. Conclusions: The study reveals significant differences in weight-bearing outcomes after ORIF of supracondylar intercondylar femur fractures. C1 fractures showed positive recovery, while C2 and C3 required extended rehabilitation. The study emphasizes fracture classification and personalized treatment for improved patient outcomes.